2017
DOI: 10.1038/s41598-017-10331-z
|View full text |Cite
|
Sign up to set email alerts
|

Stable reconstruction of the (110) surface and its role in pseudocapacitance of rutile-like RuO2

Abstract: Surfaces of rutile-like RuO2, especially the most stable (110) surface, are important for catalysis, sensing and charge storage applications. Structure, chemical composition, and properties of the surface depend on external conditions. Using the evolutionary prediction method USPEX, we found stable reconstructions of the (110) surface. Two stable reconstructions, RuO4–(2 × 1) and RuO2–(1 × 1), were found, and the surface phase diagram was determined. The new RuO4–(2 × 1) reconstruction is stable in a wide rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 56 publications
(97 reference statements)
1
28
0
Order By: Relevance
“…We name the predicted reconstructions using the stoichiometry difference between the whole structure and substrate. This nomenclature is standard and was used in a number of previous works 42,43 . Four stable reconstructions were predicted, Cl 6 -( × ), Cl 4 -(1 × 1), NaCl-(1 × 1), and Na 2 -(1 × 1), of which only one has both sodium and chlorine in its surface composition, while the rest of them have either pure chlorine or pure sodium surfaces (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We name the predicted reconstructions using the stoichiometry difference between the whole structure and substrate. This nomenclature is standard and was used in a number of previous works 42,43 . Four stable reconstructions were predicted, Cl 6 -( × ), Cl 4 -(1 × 1), NaCl-(1 × 1), and Na 2 -(1 × 1), of which only one has both sodium and chlorine in its surface composition, while the rest of them have either pure chlorine or pure sodium surfaces (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of β-NiOOH [53], an active component of the highly active catalyst for water oxidation, was fully established thanks to CSP. Likewise, a newly predicted reconstruction of the (110) surface of rutile-type RuO2 [54] has explained the extraordinary pseudocapacitance of RuO2 and established that it is partly due to a surface redox reaction. A Li7Ge3 phase was firstly proposed in a CSP study [55], and the structure was later observed in experiments [56].…”
Section: [H1] Introductionmentioning
confidence: 94%
“…Orientations that were considered in this step are β-Ga2O3 (312), (11 1 ), (312), (51 2 ), (110), and (310) and θ-Al2O3 (51 2 ). USPEX calculations have been already calculated in step (c) for θ-Al2O3 (51 2 ) and has an Esurf higher than a competing surface, thus no additional calculation is necessary on this orientation that is known to be inaccessible.…”
Section: Gamentioning
confidence: 99%